Genomic Characterization of Mutli-Drug Resistant Pseudomonas aeruginosa Clinical Isolates: Evaluation and Determination of Ceftolozane/Tazobactam Activity and Resistance Mechanisms - Bitar, Ibrahim; Salloum, Tamara; Merhi, Georgi; Hrabak, Jaroslav; Araj, George F.; Tokajian, Sima (Frontiers in Cellular and Infection Microbiology, 2022)
Resistance to ceftolozane/tazobactam (C/T) in Pseudomonas aeruginosa is a health concern. In this study, we conducted a whole-genome-based molecular characterization to correlate resistance patterns and β-lactamases with C/T resistance among multi-drug resistant P. aeruginosa clinical isolates. Resistance profiles for 25 P. aeruginosa clinical isolates were examined using disk diffusion assay. Minimal inhibitory concentrations (MIC) for C/T were determined by broth microdilution. Whole-genome sequencing was used to check for antimicrobial resistance determinants and reveal their genetic context. The clonal relatedness was evaluated using MLST, PFGE, and serotyping. All the isolates were resistant to C/T. At least two β-lactamases were detected in each with the blaOXA-4, blaOXA-10, blaOXA-50, and blaOXA-395 being the most common. blaIMP-15, blaNDM-1, or blaVIM-2, metallo-β-lactamases, were associated with C/T MIC >256 μg/mL. Eight AmpC variants were identified, and PDC-3 was the most common. We also determined the clonal relatedness of the isolates and showed that they grouped into 11 sequence types (STs) some corresponding to widespread clonal complexes (ST111, ST233, and ST357). C/T resistance was likely driven by the acquired OXA β-lactamases such as OXA-10, and OXA-50, ESBLs GES-1, GES-15, and VEB-1, and metallo- β-lactamases IMP-15, NDM-1, and VIM-2. Collectively, our results revealed C/T resistance determinants and patterns in multi-drug resistant P. aeruginosa clinical isolates. Surveillance programs should be implemented and maintained to better track and define resistance mechanisms and how they accumulate and interact.